Attitudes of medical students towards euthanasia in a multicultural setting - Adchalingam, K.; Kong, W.H.; Zakiah, M.A.; Zaini, M.; Wong, Y.L.; Lang, C.C. (Malaysian Medical Association, 2005)
A cross-sectional survey of 400 medical students of multicultural backgrounds at the University of Malaya was conducted to understand their attitudes towards euthanasia and factors related to medical decisions and ethical reasoning concerning the prolongation of life, the right to die and euthanasia. The student respondents completed self-administered questionnaires that comprised of twelve questions with multiple stems addressing personal perceptions, knowledge, attitudes, and decisions about euthanasia and the relief of suffering. The majority of respondents (52) were for the withdrawal of active therapy in a patient suffering from a terminal painful disease while 48 of them were against it. Seventy-one percent of the students involved in the study were against the idea of active euthanasia i.e. the administration of a lethal injection. However, 27 of the respondents felt that there was a moral justification to assist patients to die. Thirty-two percent of the respondents favoured the legalization of euthanasia in Malaysia while 67 of them were strongly against it. The majority (61) of respondents would not practice euthanasia as a doctor nor would they have performed on themselves if or when it became legal. The main issue surrounding euthanasia that concerned the respondents was the misuse of it by unethical practitioners and they felt that further debate on the matter was essential, both within the local and international communities.